Linear distribution processes. (1998) - Bel, L.; Oppenheim, G.; Robbiano, L.; Viano, M. C.
Abstract : In this paper, we propose a generalization of continuous-time processed defined by X t = ∫ f ( t − s ) d W s, to the case of f being a distribution. We give a necessary and sufficient condition for f, such that the obtained process is a second order distribution process. We study the moments and the regularity of these processes. In addition, we investigate a generalization to processes with stationary increments.